Penerapan Perilaku Hidup Bersih dan Sehat (PHBS) Di Lingkungan Pondok Pesantren Di Masa Pandemi Covid-19 - Siti Aisyah; Herni Sulastien; Siti Zuraida Muhsinin; Irni Dwiastiti Irianto; Eva Zulfa; Diny Kusumawardani; Erniawati Pujiningsih; Zaini Z; Musniati M (Idea Pengabdian Masyarakat, 2022)
The COVID-19 pandemic is a problem in all aspects of life, health impacts, economic impacts, including the impact of education, Islamic boarding schools cannot be separated from this impact. Community service activities regarding the Implementation of Clean and Healthy Living Behavior (CHLB) in Islamic boarding schools are expected to be able to suppress the transmission of COVID-19 in Islamic boarding schools. This activity hopes that students as pesantren residents have knowledge and are able to apply PHBS in the Islamic boarding school environment to prevent the transmission of COVID-19. The purpose of this community service activity is to provide Health Education on the Implementation of Clean and Healthy Life Behavior (CHLB) during the Covid 19 pandemic at the Manba'ul Ulum Gerung Islamic Boarding School, West Lombok. The methods used are lectures, discussions, simulations, giving leaflets to participants and tests. Activities by distributing questionnaires to activity participants. The results of the activity to increase the understanding of students, where in 30 people out of 45 students who took part in the activity, while for the 6-step handwashing demo for students, it was seen that the students were able to practice well, reaching 77.8% of 45 students.